Activity Test of Extracts of Phyllantus Herbs (Phyllantus niruri L.) and Black Seeds (Nigella sativa L.) to The Active Cutaneous Anaphylactic Reaction in Male Wistar Rats in The Induction of Ovalbumin - Arisma Nuri Pebryana; Gunawan Pamudji Widodo; Yul Mariyah (Jurnal Farmasi Indonesia, 2014)
Anaphylactic reactions is caused by repeated exposure to the same allergen mediated by specific IgE attached to mast cell and basophils wall. The administration of Phyllantus niruri L. and Nigella sativa L. have function as antiinflamation and immunomodulator. The study was purposed to prove the effect of ethanol extract of Phyllantus herbs and black seeds as inhibitors of active cutaneous anaphylactic. This study used 25 rats. Allergic rats was induced by ovalbumin (OVA) 0,1% and 0,25% in Al(OH)31% subcutaneously. Rats were divided into 5 groups : CMCNa 0,5% (negative control), sodium cromolyn 2 mg/kg BB (positive control), a single dose of Phyllantus herbs 81 mg/kg BB, a single dose of black seeds 30 mg/kg BB, the combination dose of Phyllantus herbs and black seeds (40,5:15 mg/kg BB). On the days 21th, backs rats were shaved 2,5 x 4 cm, and it were injected by evans blue 1,5%. The analyzed data was the blue pigmented areas. The result showed that treatment groups was differed significantly the negative and positive control group (p<0,05). The combination of ethanol extract phyllantus herbs and black seeds provide the most effective barrier anaphylaxis because it’s ability to inhibit the activation of mast cell adequately.